2015
DOI: 10.4018/ijdet.2015070101
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Mapping on the Learning Analytics Field and Its Analysis in the Massive Open Online Courses Context

Abstract: Learning Analytics (LA) is a field that aims to optimize learning through the study of dynamical processes occurring in the students' context. It covers the measurement, collection, analysis and reporting of data about students and their contexts. This study aims at surveying existing research on LA to identify approaches, topics, and needs for future research. A systematic mapping study is launched to find as much literature as possible. The 127 papers found (resulting in 116 works) are classified with respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
0
19
0
2
Order By: Relevance
“…Learning analytics over the years faces challenging demands and difficulties when applied in MOOC contexts [5], but as Knox [6] mentioned, learning analytics has a strong potential for discovery when it is applied to MOOC datasets. There were few research studies that combine learning analytics practices in MOOCs [7,8,9,10].…”
Section: Related Studymentioning
confidence: 99%
“…Learning analytics over the years faces challenging demands and difficulties when applied in MOOC contexts [5], but as Knox [6] mentioned, learning analytics has a strong potential for discovery when it is applied to MOOC datasets. There were few research studies that combine learning analytics practices in MOOCs [7,8,9,10].…”
Section: Related Studymentioning
confidence: 99%
“…In achieving this goal, researchers, educators, and instructional designers will be able to capture the multifaceted nature of such alternative learning experiences, as well as the patterns and the interrelationships that occur between the trainees and the learning context. Despite the growing number of studies in educational technology and the evidence gained by combining different domains [7,12], the investigation of the potential of AR combined with LA is still lacking. Similarly, no tools have been identified that can contribute toward the evaluation of such practices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, [10] introduced tools that could support instructional designers to develop learning scenarios and orchestrate teaching strategies for multilayered activities. Others [11,12] focused on the improvement of the services that massive online open courses (MOOCs) offer. Some researchers [13] have introduced review tools and analysis protocols for students' and teachers' interactions to support the process of reflection on the applied teaching strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions (devising precise actions to "shape the learning environment") (p. 5) However, it is easy to be caught up in a particular taxonomy, the specifics of a project, or one article's perspective. Data can derive from different sources or technologies, like Learning Management Systems (LMS); Digital Learning Environments (DLE); MOOCs (Moissa, Gasparini, & Kemczinski, 2015); and social networks, web tools, or student information systems (SIS); as well as from surveys, course evaluations, or self-reporting. Data can be about students interacting with other students, mentors, teachers, learning materials, and even learning environments (location, temporal data; Avella et al, 2016).…”
Section: A Simplified Storymentioning
confidence: 99%
“…6). An abundance of overview and introductory articles (Avella et al, 2016;Clow, 2013;Sclater, Peasgood, & Mullan, 2016;Ferguson et al, 2016;Haythornthwaite, de Laat, & Dawson, 2013;Pardo, Dawson, Gašević, & Steigler-Peters, 2016;Sundorph & Mosseri-Marlio, 2016;Swan, 2012) and literature reviews (Ferguson, 2012b;Moissa, Gasparini, & Kemczinski, 2015;Sclater, Peasgood, & Mullan, 2016;Sergis & Sampson, 2017) attempt to get a handle on this exponentially growing field, its key concepts, potentials, and limitations, as well as on strategies for its implementation and adoption.…”
Section: Introductionmentioning
confidence: 99%